The N-terminal Domain of the t-SNARE Vam3p Coordinates Priming and Docking in Yeast Vacuole Fusion - Laage, Rico (The American Society for Cell Biology, 2001)
Homotypic fusion of yeast vacuoles requires a regulated sequence of events. During priming, Sec18p disassembles cis-SNARE complexes. The HOPS complex, which is initially associated with the cis-SNARE complex, then mediates tethering. Finally, SNAREs assemble into trans-complexes before the membranes fuse. The t-SNARE of the vacuole, Vam3p, plays a central role in the coordination of these processes. We deleted the N-terminal region of Vam3p to analyze the role of this domain in membrane fusion. The truncated protein (Vam3ΔN) is sorted normally to the vacuole and is functional, because the vacuolar morphology is unaltered in this strain. However, in vitro vacuole fusion is strongly reduced due to the following reasons: Assembly, as well as disassembly of the cis-SNARE complex is more efficient on Vam3ΔN vacuoles; however, the HOPS complex is not associated well with the Vam3ΔN cis-complex. Thus, primed SNAREs from Vam3ΔN vacuoles cannot participate efficiently in the reaction because trans-SNARE pairing is substantially reduced. We conclude that the N-terminus of Vam3p is required for coordination of priming and docking during homotypic vacuole fusion.